Oscular system changes and functional state of endothelium in systemic vasculitides - N P Shilkina; O A. Molodkina; A A Vinogradov (Научно-практическая ревматология)
Objective. To assess by noninvasive methods degree, character and relationship of structural and functional endothelium state disturbances in different regions of vascular bed in systemic vasculitides. Material and methods. 65 pts with systemic vasculitides were examined: 20 with hemorrhagic vasculitis (HV), 20 — with thromboangitis obliterans (TO), 10 — with polyarteritis nodosa (PN), 15 — with Takayasu arteritis (ТА). 30 conditionally healthy persons were included in the control group. Carotid angioscanning with intima-media complex thickness (IMT) measurement and functional tests on brachial artery under sonographic control using SONOS-1500 apparatus with assessment of endothelium-dependent and endothelium- independent vasodilatation were performed. Intracutaneous blood flow was examined by laser Doppler flowmetry with functional tests using LAKK-01 apparatus. Results. Examination of common carotid arteries showed significant increase of IMP in pts with PN and ТА. Pts with HV and TO did not differ from control. Endothelium-dependent vasodilatation was decreased in all groups of pts. The most prominent changes were revealed in ТА and TO. Response to nitroglycerine was normal only in pts with TO. In other groups it was decreased. Endothelium sensitivity to reactive hyperemia was decreased. Hyperemic type of microcirculation prevailed in groups with systemic vasculitides but in HV group microcirculation was mainly normal. Capillary blood flow reserve was significantly lower in PN and TO. Correlation relationship was revealed between main IMP, brachial artery reactivity measures and skin microcirculation. Conclusion. Structural and functional endothelium state disturbances of different regions of vascular bed revealed in systemic vasculitides are interconnected what proves their participation in endothelium damage in these diseases.